2017
DOI: 10.1089/jwh.2015.5634
|View full text |Cite
|
Sign up to set email alerts
|

Detrimental Effects of Higher Body Mass Index and Smoking Habits on Menstrual Cycles in Korean Women

Abstract: This study substantiated that menstrual irregularity was closely associated with higher BMI and smoking habits in nondiabetic Korean women. Weight loss and smoking cessation should be recommended to promote women's reproductive health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 66 publications
0
12
1
Order By: Relevance
“…This finding is in line with the findings of Sadler and colleagues in a cross-sectional study on 974 women in the UK [43] and with the recent finding of Isgin-Atici and colleagues who found no significant differences in anthropometric measurements between PMS cases and their counterpart controls in Turkey [31]. However, this contradicts reports in Pakistani, Korean, Iran, and US adult females, in which high BMI, body fat and visceral fat were risk factors for reporting the prevalence and severity of PMS [55,56,57,58] and menstrual irregularity [59]. Nonetheless, this can be explained by the fact that the average BMI for our participants was within the normal range, with the least number of participants having a high BMI.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This finding is in line with the findings of Sadler and colleagues in a cross-sectional study on 974 women in the UK [43] and with the recent finding of Isgin-Atici and colleagues who found no significant differences in anthropometric measurements between PMS cases and their counterpart controls in Turkey [31]. However, this contradicts reports in Pakistani, Korean, Iran, and US adult females, in which high BMI, body fat and visceral fat were risk factors for reporting the prevalence and severity of PMS [55,56,57,58] and menstrual irregularity [59]. Nonetheless, this can be explained by the fact that the average BMI for our participants was within the normal range, with the least number of participants having a high BMI.…”
Section: Discussionmentioning
confidence: 99%
“…Many studies have reported an association of smoking with increased premenstrual symptoms [13,70,71] and menstrual irregularity [59], other menstrual problems and miscarriage [72] with smoking for 5 or more years was associated with an increased prevalence of such symptoms. Moreover, one study showed that smoking status and depressive symptoms/anxiety were related to a higher menstrual symptom questionnaire score [70].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported associations between obesity and menstrual status [11,12]. To our knowledge, no previous study has evaluated the association of menstrual status with different obesity phenotypes.…”
Section: Introductionmentioning
confidence: 99%
“…Cigarette smoke contains several reproductive toxicants, and the adverse effect of smoking on women's reproductive health is now well established. Besides causing adverse birth outcomes, smoking has various negative effects on nonpregnant women's reproductive health, including infertility, sub‐fecundity, younger menopausal age and menstrual disorders 1,2 . Active smoking reduces the follicular phase length by decreasing progesterone levels 3 and increases the risk of primary dysmenorrhea 4,5 and premenstrual syndrome (PMS) 6,7 .…”
Section: Introductionmentioning
confidence: 99%